Fecal Cortisol Metabolites Indicate Increased Stress Levels in Horses During Breaking-In: A Pilot Study - Julia Krieber; Aurelia C. Nowak; Jakob Geissberger; Oliver Illichmann; Sabine Macho-Maschler; Rupert Palme; Franziska Dengler (Animals)
Sport horses are frequently exposed to situations that were identified as stressors, indicated by an increased cortisol release, which might impair animal welfare. However, while many studies deal with the impact of exercise, transport, and competition on stress in horses, little is known about the early phase of a horse’s sports career and studies investigating the stress level of young horses during breaking-in are limited. To compare stress levels in unridden horses, horses during breaking-in, and horses in training we collected fecal samples of young, unridden horses (n = 28) and of horses in different training stages (n = 13) and measured fecal cortisol metabolite (FCM) concentrations. Our preliminary results showed that FCM concentrations of unridden horses were significantly lower than those of horses in training (Mann–Whitney rank sum test, p < 0.001). Particularly in the first year under the saddle FCMs were significantly higher than in unridden horses (one way ANOVA + post hoc Holm–Sidak test, p < 0.05), with a tendency for FCM levels to decrease with time in training. Furthermore, we observed that within the group of ridden horses there was a larger range of variability in FCM levels, suggesting individual variations regarding their ability to deal with (training-induced) stress. These results indicate that breaking-in is a stressful time for young horses, underlining the importance of carrying out the initial training as carefully as possible.